Role of water in maize starch gelatinization: an study by Differential Scanning Calorimetry (2010)
The thermal behavior of corn starch (Sigma Aldrich) was studied through differential scanning calorimetry (DSC). The endothermic peak observed in the DSC profile is associated with the transition process of starch gelatinization. The initial phase of the process and the range in which it occurs is governed mainly by the concentration of the starch in solution. In this investigation it is demonstrated that the parameters related to the method of observation, in a DSC analysis influence when determining the gelatinization of corn starch. In this way, the temperature of the transition peak, the gelatinization enthalpy and the gelatinization temperature range are the parameters under study when the sample humidity and heating rate are varied with a homogeneous grain size. For the analyzes, values ​​were taken of humidity of 60, 65, 70, 75 and 80% (w / w), for a heating rate of 2, 5 and 10 ° C / min. Similarly, for a fixed humidity value (80%), a heating rate of 2, 5, 7, 10 and 15 ° C / min was used. The results indicate that the amount of water significantly influences the enthalpy of gelatinization of the process, but the temperature of the Tp peak of the endotherm remains constant. The value of the enthalpy decreases as the amount of water increases.The variations are also dependent on how quickly the transformation takes place. The analyzes allowed corroborating that this transition in elalmidon is dependent on extrinsic factors during the process. This knowledge about starch gelatinization is useful for optimizing industrial processes derived from it.